Peran Guru Dalam Mengatasi Kesulitan Belajar Siswa Di SDIT Alfityah Pekanbaru - Wismanto Wismanto; Sakban Sakban; Azizah Tulfauziah; Viona Afrila; Selvina Zulpa; Mutiara Khairunnisa; Nadya Elpita Sari (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2024)
Al Fityah Elementary School students and girls experience various learning difficulties such as difficulty concentrating or focusing on the material being taught, difficulty communicating thoughts and opinions to other people, difficulty communicating well, difficulty solving complicated problems that require students to think critically, and difficulty Arranging words and sentences correctly, this is interesting. This research aims to describe the types of learning difficulties of students at SDIT Al Fityah Pekanbaru, in order to understand the steps taken by teachers in overcoming the learning difficulties of participants at SDIT Al Fityah Pekanbaru. This research uses a qualitative approach. Teachers take steps to make student learning easier, namely directing and paying attention to students who experience learning difficulties, utilizing the learning environment, presenting assignments and exercises to create a desire for independent learning in students, directing students to study in groups using interesting learning. role models and rewards for students so that students feel happy and motivated in learning. Teachers also connect the material taught with students' daily lives, so that students easily understand the concepts being taught.